The association between continual, year-round hunting and bellowing rate of bison bulls during the rut - Sarno,Ronald J.; Grigione,Melissa M.; Higa,Alessandra; Childers,Eddie; Ecoffey,Trudy (PeerJ, 2017)
The impact of hunting (selective harvest, trophy hunting) on the demography of mammals is well documented. However, despite continual year-round hunting of bison in some populations, little is known about how the behavior of survivors may be altered. Therefore, in this initial study, we used focal-animal observations in adjacent populations of continually hunted and protected Plains bison (Bison bison bison) in western South Dakota, to examine the potential impact of hunting on bellowing rate—an important behavior that serves to intimidate rival bulls and potentially influences mate choice by females. In addition to hunting, we investigated how the number of attendant males, number of adult females, group size, and number of days from the start of rut influenced bellowing rate. Bulls bellowed an order of magnitude more often in the protected population than in the hunted populations, whereas bellowing rate was not significantly different in the hunted populations. Hunting was significantly and negatively associated with bellowing rate, while all other predictors were found to be positively associated with bellowing rate. Furthermore, the impact of hunting on bellowing rate became more pronounced (i.e., dampened bellowing rate more strongly) as the number of attendant males increased. Changes in bellowing behavior of bulls (and possibly mate choice by cows) can alter breeding opportunities. Therefore, our data suggest the need for studies with broader-scale geographical and temporal replication to determine the extent that continual year-round hunting has on bellowing rate of bison during the rut. If reduced bellowing is associated with human hunting on a larger scale, then wildlife managers may need to adjust hunting rate and duration, timing (season), and the time lag between hunting events in order to insure that bison are able to express their full repertoire of natural mating behaviors.
Keywords: Management; Bellows; Sensitization; Demography; Vocalizations; Hunting